Long non-coding RNAs as novel diagnostic and therapeutic targets in kidney disease - Qin Zhou (KeAi Communications Co., Ltd., 2019)
Long non-coding RNAs (lncRNAs) have critical roles in the development of many diseases including kidney disease. An increasing number of studies have shown that lncRNAs are involved in kidney development and that their dysregulation can result in distinct disease processes, including acute kidney injury (AKI), chronic kidney disease (CKD), and renal cell carcinoma (RCC). Understanding the roles of lncRNAs in kidney disease may provide new diagnostic and therapeutic opportunities in the clinic. This review provides an overview of lncRNA characteristics, biological function and discusses specific studies that provide insight into the function and potential application of lncRNAs in kidney disease treatment. Keywords: Long non-coding RNAs, Kidney disease, Renal inflammation, Renal fibrosis, Diabetic nephritis, Renal cell carcinoma